Anxiety, depression, somatization and experiential avoidance indicators in peruvian university students in quarantine by COVID-19 - Sánchez Carlessi, Héctor Hugo (2021)
Introduction: The COVID-19 quarantine has greatly affected university students in Peru, generating a series of physical, psychological and behavioral effects. Objective: To determine the factors associated with anxiety, depression, somatization and experiential avoidance in peruvian university students quarantined by COVID-19. Methods: A cross-sectional observational study was carried out. The sample was made up of 1264 university students from various departments of Peru, anxiety, depression, somatization and experiential avoidance were taken as dependent variables, which were evaluated with the questionnaire "The Inventory of unadjusted psychosocial behavior, in the presence of COVID-19 in the Peruvian population” and the AAQ II, for the statistical analysis the chi square was used Results: More than half of the university students in Peru present between 3 and 6 of the 6 anxiety indicators, and this same number of depression indicators is presented by 45% of the sample. 30% of the sample has between 3 and 6 indicators of somatization and 40.3% of the sample is located in the middle upwards on the experiential avoidance scale. Conclusions: There are differences in the levels of anxiety, somatization and experiential avoidance between men and women, it was also found that older students had lower levels of anxiety, depression and experiential avoidance, but not in somatization.